A case of autosomal recessive hypercholesterolemia caused by a new variant in the LDL receptor adaptor protein 1 gene - Vaverkova, Helena; Tichy, Lukas; Karasek, David; Freiberger, Tomas (Journal of clinical lipidology, 2019)
We report a new variant in the LDLRAP1 gene associated with autosomal recessive hypercholesterolemia in a woman of central European ancestry.
Keywords: dospělí; Humans; Adaptor Proteins, Signal Transducing; lidé středního věku; Pedigree; rodokmen; Middle Aged; genetická variace; mužské pohlaví; adaptorové proteiny signální transdukční; Hypercholesterolemia; Adult; heterozygot; ženské pohlaví; Genetic Variation; lidé; Heterozygote; hypercholesterolemie; Aged; senioři; Male; Female